2012
DOI: 10.1108/01439911211201582
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous industrial mobile manipulation (AIMM): past, present and future

Abstract: PurposeThe purpose of this paper is to provide a review of the interdisciplinary research field, autonomous industrial mobile manipulation (AIMM), with an emphasis on physical implementations and applications.Design/methodology/approachFollowing an introduction to AIMM, this paper investigates the missing links and gaps between the research and developments efforts and the real‐world application requirements, in order to bring the AIMM technology from laboratories to manufacturing environments. The investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 56 publications
0
53
0
Order By: Relevance
“…Here, a brief overview of the current state of the art in autonomous mobile manipulation (both, industrial, as well as service robotics) will be presented. A thorough review of past research in the field of autonomous industrial mobile manipulation can be found in Bøgh et al 6 and Hvilshøj et al 7 In the service robot domain, the PR2 is applied to perform manipulation tasks in a real home by Ciocarlie et al 8 The authors state that mobile robots are not able to achieve the level or reliability needed in real living environments. Thus, teleoperating the robot by a human is a vital component of the system concept.…”
Section: Related Workmentioning
confidence: 99%
“…Here, a brief overview of the current state of the art in autonomous mobile manipulation (both, industrial, as well as service robotics) will be presented. A thorough review of past research in the field of autonomous industrial mobile manipulation can be found in Bøgh et al 6 and Hvilshøj et al 7 In the service robot domain, the PR2 is applied to perform manipulation tasks in a real home by Ciocarlie et al 8 The authors state that mobile robots are not able to achieve the level or reliability needed in real living environments. Thus, teleoperating the robot by a human is a vital component of the system concept.…”
Section: Related Workmentioning
confidence: 99%
“…Lisa et al [7] presents assembly manipulation of small objects by dual-arm using stereo camera system. Hvilshoj et al [8] deals with the past, present and future of autonomous industrial mobile manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, they are used in relatively fixed and inflexible working conditions. Recently, diverse sensors including camera and laser-based 3D sensing systems have been used to provide greater flexibility to the robot thorough visual feedback [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Lisa et al [7] presents assembly manipulation of small objects by robot with dual-arm using stereo camera system. Hvilshoj et al [8] represents good reviews including the past, present and future of autonomous industrial mobile manipulation.…”
Section: Introductionmentioning
confidence: 99%